TAKTIK INTEGRATED MARKETING COMMUNICATIONS PADA UMKM PENGRAJIN BATIK SOLO - Rina Tanti Astik Putri; Janette Maria Pinariya; Ghina Dintya Maulidianty (Metacommunication: Journal of Communication Studies, 2022)
The research carried out is the application of Integrated Marketing Communication (IMC) which includes digital/internet marketing, sales promotion and personal selling at small and medium-sized enterprises (SMEs) batik craftsmen Solo HR Boutique. This study aims to determine the IMC tactics carried out by batik craftsmen Solo HR Boutique in introducing traditional batik with a modern touch. The method in this research is descriptive qualitative. The data used are semi-structured in-depth interviews and document collection. Miles and Hubermen data analysis is a technique that will be used in this study. The results show that overall IMC tactics used by HR Boutique are interrelated and work well but have advantages and disadvantages. The advantage is that HR Boutique is able to create awareness of its brand so that it can grow positive word of mouth (WOM) and make HR Boutique a successful SME. The drawbacks are the lack of variety and creativity in creating marketing content and the lack of variety of batik designs.Kata Kunci: Komunikasi Pemasaran, IMC, Batik Solo